Exopolysaccharide from Trichoderma pseudokoningii induces the apoptosis of MCF-7 cells through an intrinsic mitochondrial pathway. (20th January 2016) - Wang, Guodong; Liu, Chunyan; Liu, Jun; Liu, Bo; Li, Ping; Qin, Guozheng; Xu, Yanghui; Chen, Ke; Liu, Huixia; Chen, Kaoshan
Highlights: Exopolysaccharide (EPS) could inhibit the proliferation of MCF-7 cells and induce lactic dehydrogenase release in vivo. EPS induces apoptosis and arrests MCF-7 cells in S phase of the cell cycle. EPS may trigger apoptosis through an intrinsic mitochondrial apoptotic pathway. Abstract: In this study, we reported the anticancer efficacy of exopolysaccharide (EPS) derived from Trichoderma pseudokoningii, on human breast cancer MCF-7 cells. Our results showed that EPS inhibited the proliferation of MCF-7 cells and induced lactic dehydrogenase release by inducing apoptosis and cell arrest at S phase. Further study revealed that EPS-induced apoptosis of MCF-7 cells was associated with alteration of nuclear morphology, disruption of mitochondrial membrane potential and accumulation of intracellular reactive oxygen species. Sequentially, EPS increased the activation of caspase-9 and caspase-3 in a dose-dependent manner; however, caspase-8 remained intact. Western blot analysis revealed that EPS increased the ratio of Bax/Bcl-2 and promoted the release of cytochrome c into the cytoplasm. Taken together, these findings provided evidence that EPS induced the apoptosis of MCF-7 cells through an intrinsic mitochondrial apoptotic pathway and that EPS may therefore be considered as an effective adjuvant agent against human breast cancer.